THE RELIGIOUS POLICY OF THE SOVIET STATE IN UZBEKISTAN: THEORETICAL AND LEGAL FOUNDATIONS. (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comprehensive analysis of the theoretical and legal foundations of religious policy in the Republic of Uzbekistan during the Soviet period. The author firstly examines the role of religion in state governance during the Soviet era and its impact on religious organizations. Additionally, the legal norms regarding religious freedoms and restrictions, along with their practical implementation, are studied. The article sheds light on the ideological policies conducted by the Soviet government and the relationships between religious communities, developing essential conceptual principles related to the development of religious policy in the country.